Glutamatergic signaling between neurons and oligodendrocyte lineage cells: Is it synaptic or non‐synaptic?. Issue 11 (5th April 2019) - Kula, Bartosz; Chen, Ting‐Jiun; Kukley, Maria
ABSTRACT: Fast chemical synaptic transmission is a major form of neuronal communication in the nervous system of mammals. Another important, but very different, form of intercellular communication is volume transmission, which is a slower non‐synaptic signaling. The amino acid glutamate is the most abundant excitatory neurotransmitter in the nervous system, which mediates both synaptic and non‐synaptic signaling via ionotropic and metabotropic glutamate receptors. Intriguingly, neurons establish glutamatergic synapses also with oligodendrocyte precursor cells (NG2 + ‐glia). Moreover, neuronal activity and glutamate receptors play an important role in the development and functionality of oligodendrocytes and their precursors in vivo. Yet, molecular characteristics and functional significance of neuron–glia synapses remain poorly understood, and it is unclear how glutamate receptors mediate the effects of neuronal activity on the oligodendrocyte lineage cells. In this review, we discuss what is known with regard to synaptic and non‐synaptic glutamatergic signaling between neurons and oligodendrocyte lineage cells, what can be suggested based on the current state of knowledge, and what is fully unknown and requires new research. Main points: Oligodendroglia express glutamate receptors which may be activated by synaptically released glutamate or volume transmission. Glutamatergic neuron‐oligodendroglia signaling is important for development and functionality of oligodendrocytes and their precursors.